Antihypertensive medications adherence and associated uncontrolled blood pressure among hypertensive patients in Ethiopia: Systematic review and meta-analysis. (2022) - Desta, Melaku; Yibeltal, Desalegn; Memiah, Peter; Ayenew, Temesgen; Mulugeta, Henok; Gedefaw, Mihretie; Bewket Kidanie, Bekalu; Birhanu, Molla Yigzaw; Tessema, Zenaw; Mengist, Belayneh; Alene, Muluneh; Simieneh, Muluye Molla; et al.
Highlights: This meta-analysis revealed that the adherence of antihypertensive medications and its association with uncontrolled blood pressure. Two out of every three hypertensive patients adhere to medication regimens. Knowledge of hypertension and comorbidities increased odds of antihypertensive medication adherence. Adherence toward an antihypertensive medication regimen reduced the risk of uncontrolled blood pressure. Education on medications adherence and screening for comorbidities aids in reducing uncontrolled blood pressure. Abstract: Background: Despite remarkable progress in the reduction of communicable diseases, non-communicable diseases still pose a threat worldwide. One such non-communicable disease is hypertension which remains a major public health problem in Sub-Saharan Africa. Adherence to antihypertensive medication regimens is paramount in reducing its burden. Study findings in Ethiopia regarding adherence to antihypertensive medications and their impact on blood pressure control have been inconclusive and inconsistent. This systematic review and meta-analysis aimed to estimate the pooled adherence to antihypertensive medications and their association with uncontrolled blood pressure among hypertensive patients in Ethiopia. Methods: International databases including PubMed, Web of Science, SCOPUS, CINAHL, PsycINFO, Google Scholar, Science Direct, and the Cochrane Library were systematically searched. All identified observational studies and/or predictors were included, and I 2 statistics were used to assess the heterogeneity of the studies. A random-effects model was computed to estimate the pooled adherence level and its association with uncontrolled blood pressure. Results: The random-effect meta-analysis showed that a pooled national antihypertensive medication adherence among hypertensive patients was 65.1% (95% CI: 61.6%, 68.6%). The highest medications adherence was 83.5% (95% CI: 77.0%, 89.9%) occurring in the Somali Region with the lowest medication adherence being 58.5% (95% CI: 47.7%, 69.3%) in the Tigray Region. The meta-analysis suggested a significant increase in medication adherence among patients who had good knowledge of hypertension [POR = 4.26 (95% CI: 4.26 (2.70, 6.72)] and 2.54 times increase in the odds among patients who had co-morbidities [POR = 2.54 (95% CI: 1.06, 6.07)]. This meta-analysis also revealed a 51% reduction of uncontrolled blood pressure among patients who adhered to an antihypertensive medication regimen [POR = 0.49 (95% CI: 0.34, 0.69)]. Conclusions: Two of every three hypertensive patients have adhered to a medication regimen that was associated with reduced odds of uncontrolled blood pressure. Therefore, interventions of highest priority to increase antihypertensive medication adherence are aimed at improving knowledge of hypertension and identifying or screening hypertensive patients who have comorbidities. The Federal Ministry of Health and other relevant stakeholders should increase efforts in the prevention of uncontrolled blood pressure through education on adherence to medication regimens with a focus on modifiable risk factors.